2001
DOI: 10.1016/s1074-7613(01)00173-x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Duration versus Extent of TCR Occupancy on T Cell Activation

Abstract: The widely accepted kinetic proofreading theory proposes that rapid TCR dissociation from a peptide/MHC ligand allows for stimulation of early but not late T cell activation events, explaining why low-affinity TCR ligands are poor agonists. We identified a low-affinity TCR ligand which stimulated late T cell responses but, contrary to predictions from kinetic proofreading, inefficiently induced early activation events. Furthermore, responses induced by this ligand were kinetically delayed compared to its high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
231
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(254 citation statements)
references
References 52 publications
20
231
0
Order By: Relevance
“…However, preliminary comparisons of calculated data with experimental data obtained from the literature (6,19,22,23) have shown that this model was realistic. In this study, we have used this computer simulation choosing a set of initial parameters (agonistic peptide, cell sizes, and CD3 levels of expression) that are close to the conditions in vivo.…”
Section: Variability Of Cd3 Membrane Expression and T Cell Activationmentioning
confidence: 83%
See 1 more Smart Citation
“…However, preliminary comparisons of calculated data with experimental data obtained from the literature (6,19,22,23) have shown that this model was realistic. In this study, we have used this computer simulation choosing a set of initial parameters (agonistic peptide, cell sizes, and CD3 levels of expression) that are close to the conditions in vivo.…”
Section: Variability Of Cd3 Membrane Expression and T Cell Activationmentioning
confidence: 83%
“…If the number of p-MHC is restricted, serial engagement of TCR are possible (18)(19)(20). Further TCR/CD3 complexes need to be recruited from outside the synapse through surface transfer but this has to be completed during a short lag time (16,(21)(22)(23) to be efficient. Activation induces IL-2 production and membrane expression of the c chain of its receptor [CD25; (24)].…”
mentioning
confidence: 99%
“…The differences in affinity and half-life between agonists and antagonists are surprisingly small. It is also possible to find weak agonist ligands that activate through a gradual build-up of signals, culminating in full activation, but where the early points in the signaling cascade are not detectable (12). Similar models apply during thymic selection, where a long TCR-pMHC interaction leads to negative selection and shorter interactions give positive selection.…”
mentioning
confidence: 99%
“…The half-life (t 1/2 ) of the TCR/pMHC interaction must be above certain threshold to allow productive TCR signaling, as proposed by the kinetic proofreading model (11). Several studies have provided evidence supporting this notion by showing that pMHC ligands with excessively short half-lives fail to complete the signaling cascade required for T-cell activation (14)(15)(16)(17).…”
mentioning
confidence: 99%